1999
DOI: 10.1002/(sici)1522-2594(199911)42:5<849::aid-mrm4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of BOLD signal dependence on cerebral blood flow and oxygen consumption: The deoxyhemoglobin dilution model

Abstract: The relationship between blood oxygenation level-dependent (BOLD) MRI signals, cerebral blood flow (CBF), and oxygen consumption (CMR O 2 ) in the physiological steady state was investigated. A quantitative model, based on flow-dependent dilution of metabolically generated deoxyhemoglobin, was validated by measuring BOLD signals and relative CBF simultaneously in the primary visual cortex (V1) of human subjects (N ‫؍‬ 12) during graded hypercapnia at different levels of visual stimulation. BOLD and CBF respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
587
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(630 citation statements)
references
References 33 publications
34
587
2
1
Order By: Relevance
“…In this study, we continuously monitored and minimized changes in PETO 2 through the use of computerized targeting facilitated by RespirAct, and were therefore able to achieve the isolation of CO 2 effects, which is a key requirement for the experiment at hand, and constitutes a basic assumption in numerous fMRI experiments using CO 2 challenges. Our results suggest that there are no significant alterations in global CMRO 2 due to these challenges, consistent with predictions obtained using the deoxyhemoglobin dilution model (Hoge et al, 1999). Although the current measurements show an absence of substantial global CMRO 2 modulation by low levels of PETCO 2 modulation, they do not preclude the possibility of spatial heterogeneities in the CMRO 2 response to capnic challenges.…”
Section: Resultssupporting
confidence: 89%
“…In this study, we continuously monitored and minimized changes in PETO 2 through the use of computerized targeting facilitated by RespirAct, and were therefore able to achieve the isolation of CO 2 effects, which is a key requirement for the experiment at hand, and constitutes a basic assumption in numerous fMRI experiments using CO 2 challenges. Our results suggest that there are no significant alterations in global CMRO 2 due to these challenges, consistent with predictions obtained using the deoxyhemoglobin dilution model (Hoge et al, 1999). Although the current measurements show an absence of substantial global CMRO 2 modulation by low levels of PETCO 2 modulation, they do not preclude the possibility of spatial heterogeneities in the CMRO 2 response to capnic challenges.…”
Section: Resultssupporting
confidence: 89%
“…The flow and transverse relaxation data have been incorporated into a model of deoxyhemoglobin concentration, oxygen extraction, and consumption by numerous workers (Ogawa et al, 1993;Davis et al, 1998;Hoge et al, 1999;Oja et al, 1999) expressed in equation (1). The blood susceptibility-induced transverse relaxation rate, R 2 0 , is calculated from the time reversible gradient echo relaxation rate, R 2 *, and time irreversible spin echo intrinsic relaxation rate, R 2intrinsic , corrected by the loss of signal from B o homogeneity (An and Lin, 2002;Yablonskiy, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…These coupling ratios are consistent with several recent estimates of flow metabolism coupling during task activation. For example, using MR, Hoge et al (1999) reported fM/fP ratio of 0.52 for graded visual stimulation while Davis et al (1998) reported an fM/fP ratio of 0.35 using a 12 Hz visual stimulation paradigm. Using PET, Marrett and Gjedde (1997) report an fM/fP ratio of 0.37 with a 4 Hz visual stimulation protocol, while Fox and Raichle (1986) report an fM/fP ratio of 0.1 using somatosensory stimulation in their early PET studies.…”
Section: Resultsmentioning
confidence: 99%
“…When utilized together, the BOLD and perfusion signals can provide a quantitative understanding of the metabolic response to neural activity and provide insight into neurovascular coupling mechanisms (Hoge et al 1999). However, as the fMRI community has moved to higher field strengths, physiological noise has become an increasingly important confound limiting the sensitivity and the application of fMRI studies (Kruger and Glover 2001;Liu et al 2006).…”
Section: Introductionmentioning
confidence: 99%